2015
DOI: 10.2174/1568026615666150427125033
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking Studies of the Antitumoral Activity and Characterization of New Chalcone

Abstract: Phytochemical investigation of Azorella madreporica led to the isolation of four known compounds and an unknown chalcone. The structure of the new compound was identified by spectroscopy, including two-dimensional NMR techniques and comparison with published spectral data. The antioxidant activity of chalcone (compound 1) was measured using the 1,2-diphenyl-2-picryl-hydrazyl (DPPH) free radical scavenging assay, and the bioactivity was evaluated against five bacteria (Mycobacterium smegmatis ATCC 14468, clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
1
9
0
2
Order By: Relevance
“…We found that the majority of I-X sub-fractions induced a reduction of KG1 and MV4-11 cell viability in a dose and time dependent way ( Figure 3 ). These results are in accordance with previous studies reporting the cytotoxic effects of different Azorella species on a variety of solid and hematological malignancies [ 34 , 36 ], including AML [ 14 ]. Moreover, our results indicated that differences in the cytotoxic activities among I-X sub-fractions seem to be inversely associated with their in vitro antioxidant activities.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that the majority of I-X sub-fractions induced a reduction of KG1 and MV4-11 cell viability in a dose and time dependent way ( Figure 3 ). These results are in accordance with previous studies reporting the cytotoxic effects of different Azorella species on a variety of solid and hematological malignancies [ 34 , 36 ], including AML [ 14 ]. Moreover, our results indicated that differences in the cytotoxic activities among I-X sub-fractions seem to be inversely associated with their in vitro antioxidant activities.…”
Section: Discussionsupporting
confidence: 93%
“…Although the antitumor property of Azorella genus extracts were recently reported [ 14 , 34 , 36 ], AG Wedd. extracts have not yet been extensively explored.…”
Section: Discussionmentioning
confidence: 99%
“…Sung et al reported the cytotoxic activity of methanolic extract of A. compacta and its ability to induce apoptosis on leukemic HL60 cells [ 34 ]. Previously, another work described the antiproliferative activity of a new chalcone from Azorella madreporica on colon, breast, and prostate cancer cells [ 56 ]. All these data indicate the Azorella genus as a possible source of natural agent against different cancer types, including hematologic malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Since food provides the human body with essential nutrients, such as proteins, lipids, carbohydrates and vitamins, molecular docking can be widely applied in these particular areas. Moreover, food safety issue concerning with drug residues, biotoxins and foodborne pathogens is one of the utmost importance in the food research, which is increasingly involved with molecule level study (San-Martin et al, 2015;Nakano et al, 2018;Sledz & Caflisch, 2018). It should be noted that the applications of molecular docking related to food have been growing rapidly in the last few years (as seen in Fig.…”
Section: Introductionmentioning
confidence: 99%